Converting from Seepage Irrigation to Plasticulture for Vegetable Production: A Case Study - Charles E. Barrett; Lincoln Zotarelli; Lucas G. Paranhos; Mark W. Warren (EDIS)
This article is intended to provide information to producers and Extension agents that are interested in using drip irrigation for vegetable production. Cabbage production in Florida is dominated by the use of seepage or sub-irrigation. This system has traditionally been used because it is inexpensive to maintain and simple to use. Seepage irrigation works by damming tail water ditches, pumping water into open furrows, and effectively raising the water table to a depth accessible to the crop root system (For more information see EDIS Publication #HS1217). This type of irrigation practice is almost completely unique to Florida and is possible due to the persistence of a shallow, impermeable layer in the soil profile. This system can require vast quantities of water to be pumped from the aquifer in low-rainfall years. Plasticulture, or the use of drip irrigation and plastic mulch, has been proposed as an alternative production method for cabbage production in Florida.